Pengaruh Kepemimpinan Kepala Sekolah Dan Kurikulum Merdeka Terhadap Kinerja Guru SMA Negeri Program Sekolah Penggerak - Lidya Novalita; Nur Ahyani; Syaiful Eddy (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aimed to determine the effect of principal leadership and the independent curriculum on teachers' performance in SMA Negeri Program Mobilization Schools in Kayuagung District. This research was conducted at Kayuagung 1 Public High School, Kayuagung 2 Public High School, and Kayuagung 3 Public High School. This research is a type of quantitative research. The research design used in this study is correlational. Data collection methods in this study used questionnaires, observation, and documentation. The total population in this study amounted to 137 people. Based on the calculation of the number of samples in this study, there were 58 people. Data analysis techniques use data normality tests, data linearity tests, data multicollinearity tests, t-tests, F tests, and the Coefficient of Determination. The results of this study show a positive influence of the leadership of the principal and the independent curriculum together on the performance of teachers at the State High School Program Mobilization in the Kayuagung District. This can be seen from the results of the Fcount>Ftable test. The effect is also seen from the tcount> table test results, which means that Ha3 is accepted and Ho3 is rejected. In conclusion, there is an influence of the leadership of the principal and the independent curriculum on the performance of the teachers of the State High School Program Mobilization Schools in Kayuagung District. Keywords: Leadership; Headmaster; Independent Curriculum; Teacher Performance